2006
DOI: 10.1039/b608481h
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective formation of a single-stranded helicate: Structure of a bis(palladium-allyl)quaterpyridine complex and its use in catalytic enantioselective allylic substitution

Abstract: Chiral C2-symmetric quaterpyridine L reacts with [Pd(eta3-C3H5)Cl]2 to form a chiral single-stranded helical binuclear palladium complex of formula [Pd2(eta3-C3H5)2(L)]2+; the complex can efficiently catalyze allylic substitution of 1,3-diphenylprop-2-enyl acetate with dimethyl malonate with enantioselectivity up to 85%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…[7] Among them, the helicates have gained popularity due to their applications in many areas, such as synthetic receptors, [9] liquid crystalline materials, [10] catalysis, [11] and DNA recognition. [12] Most of them rely on the coordination of transition metal cations to pyridine-or phenanthroline-containing molecular strands, and their three-dimensional structures are determined by the coordination geometry requirements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Among them, the helicates have gained popularity due to their applications in many areas, such as synthetic receptors, [9] liquid crystalline materials, [10] catalysis, [11] and DNA recognition. [12] Most of them rely on the coordination of transition metal cations to pyridine-or phenanthroline-containing molecular strands, and their three-dimensional structures are determined by the coordination geometry requirements.…”
mentioning
confidence: 99%
“…
A large number of synthetic double helices have been developed during the past few decades because of their significant aesthetic and biomimetic appeal, and several structural motifs for double helices are now available, [1][2][3][4][5][6][7][8] including the peptide analogues of DNA, [2] transition metal complexes, namely the helicates, [3,4] aromatic oligoamides, [5] amidiniumcarboxylate salt bridges, [6] and oligoresorcinols. [7] Among them, the helicates have gained popularity due to their applications in many areas, such as synthetic receptors, [9] liquid crystalline materials, [10] catalysis, [11] and DNA recognition. [12] Most of them rely on the coordination of transition metal cations to pyridine-or phenanthroline-containing molecular strands, and their three-dimensional structures are determined by the coordination geometry requirements.
…”
mentioning
confidence: 99%
“…Potts et al reported a high yield synthesis [15] that requires the cleavage of alkylthio-substituents before the final ligands can be obtained and precludes the preparation of asymmetrical analogues. Various coupling methodologies have also been developed: (i) the Ullmann reaction with copper powder at high temperature [9]; (ii) coupling of 6-halo-2,2’-bipyridines in the presence of nickel reagents [1617], some of which are chiral [1819]; and (iii) a Stille-based synthetic pathway [17,20], or a Suzuki–Miyaura cross-coupling reaction [21]. The use of triazine derivatives (which under particular conditions undergo an inverse Diels–Alder reaction) can also produce oligopyridines [22].…”
Section: Resultsmentioning
confidence: 99%
“…[11,16,17] However, when achiral ligands containing long or flexible spacers are used, formation of helicates or mesocates, or mixtures of both, is generally unpredictable. [15,18] Optically pure helicates present interesting applications as chiral molecular cages, [19] asymmetric catalysts, [20,21] and in medicinal chemistry. [16] They have been obtained by resolution of racemic mixtures, [16,22] or, more conveniently, by enantioselective self-assembly of enantiopure chiral ligands and metal cations.…”
Section: Introductionmentioning
confidence: 99%